A retrospective analysis of factors influencing readmission rates of acute traumatic subdural hematoma in the elderly: A cohort study. (2019) - Ho, Tran; Frisbie, Jacob; Wasfie, Tarik; Boyer, Jennifer J.; Knisely, Tara; Cwalina, Natalia; Barber, Kimberly; Shapiro, Brian
Abstract: Objective: Acute traumatic subdural hematomas (TSDH) readmission rate is high (27.8%) with an increase in morbidity and cost for the elderly. This study identifies risk factors affecting readmission rates for these patients and presents strategies to reduce it. Methods: A retrospective analysis was conducted including patients with TSDH admitted to our Community Hospital and followed subsequently for two years regarding readmission within 6 months of initial discharge. The following factors were compared for patients readmitted versus not readmitted: patient age, sex, number of comorbidities, anticoagulation status, surgical intervention, ICU length of stay, injury severity score, and discharge disposition. Results: A total of 167 patients were included in the study. Overall, 75 patients (44.9%) were readmitted within 6 months. Readmitted patients had an overall higher mean age (74.1 vs. 65.4, p = 0.001). Readmission with recurrent subdural hematoma was diagnosed in 32.2% of readmitted patients vs. 67.8% (p < 0.0005) with readmission for other medical complications. 80.0% of readmitted patients had more than four comorbid conditions ( p < 0.0001). Conclusion: This study identifies risk factors that affect readmission rates for patients with TSDH and establishes strategies that may help to decrease readmission. Highlights: Traumatic Subdural Hematoma has a mortality rate of approximately 40–60% even with surgical intervention. The incidence of Traumatic Subdural Hematoma has increased dramatically, especially among the elderly population. Patients diagnosed with TSDH are often readmitted either due to recurrence of the TSDH or other medical complications. Identifying risk factors affecting readmission we can reduce the rate of complications, mortality, and cost of their care.